Global trends and topics in CDK7 inhibitor research: a bibliometric analysis - Liu, Jiamin; He, Ling; Jiang, Wenjing; Xie, Ping (Frontiers in Pharmacology, 2024)
Background: CDK7 has been demonstrated to play a crucial role in the initiation and progression of malignancy. Therefore, targeting CDK7, which regulates the transcription process, has emerged as a new promising approach for treating cancer. Research on CDK7 inhibitors has significantly increased over the past two decades, with almost 600 related papers in the Web of Science Core Collection database. To effectively identify future research hotspots and potential future directions, it is crucial to systematically review and visually present the research on this topic from a comprehensive viewpoint, ensuring scientific reliability.This study performed bibliometric analysis via CiteSpace and VOSviewer scientometric analysis software to examine data on the publication of articles on CDK7 inhibitors over the past two decades; the data included country of publication, author names, institution names, scientific categories, cited journals, and keywords related to the field of CDK7 inhibitors.Results: This bibliometric analysis included 426 publications from 41 different nations, referencing a total of 15,892 sources. Research associated with CDK7 inhibitors has rapidly expanded since 2016, and the US and China are the two countries with the highest publication output among the countries and institutes that produce literature on CDK7 inhibitors. Furthermore, the US is the country that most frequently engages in international cooperation. The evolution of keywords identifying antitumor strategies related to CDK7-mediated cellular transcription processes has been the research focus in recent years.In this study, we identified research efforts and their evolving patterns and predicted advances in the CDK7 inhibitor field. The knowledge structure of CDK7 inhibitors encompasses pharmacological mechanisms, therapeutic targets, and cancer treatment strategies. The primary objectives of contemporary research are to discover the processes underlying cancer progression, identify specific signaling pathways, and develop effective clinical medicines.